Short-term trading around ex-dividend days - Karpoff, Jonathan M.; Walkling, Ralph A. (Journal of Financial Economics, 1988)
A dividend tax penalty creates profitable trading opportunities for short-term traders with sufficiently low transaction costs. In stocks with ex-dividend day returns affected by short-term trading, ex-day returns are positively correlated with transaction costs. Data from 1964–1985 indicate that short-term traders are the marginal investors in high-yield stocks, primarily since the introduction of negotiated commissions on the NYSE. Short-term trading is not evident in low-yield stocks, nor does it appear prevalent before negotiated commissions.